“I” on the web: Social penetration theory revisited - Panos, Dionysis (My University, 2014)
This research project aims to highlight how Interpersonal Communication Management Information in Computer-Mediated- Communication has changed over the years, primarily as a result of the widespread adoption of digital practices associated with the Second Internet Age, otherwise called Web 2.0 whichbecame prevalent in the latter part of the 20th century and continues to evolve today. It presents the results of an empirical research project based on data collected longitudinally (spanning the period 2002-2012) from 458 personal semi-constructed in-depth interviews with Internet users from 24 countries. The findings reveal a significant shift in users’ perceptions concerning the degree of "security" and "familiarity" of the Web between the pre- and the post- Web 2.0 eras. Additionally, the paper discusses the significant changes brought about with regard to two fundamental concepts in communication theory: the concept of the “audience”, and the long-standing dichotomy between the 'private' and 'public' spheres of social life. Based on Social Penetration Theory the paper proposes an integrative model for comprehending the mechanisms of personal information management in interpersonal communication, applicable to both online (Computer-Mediated) and offline (Face-To-Face) contexts of communication.
Keywords: Computer-mediated interpersonal communication; Private and public personal information; Self-disclosure; Social penetration theory